2004
DOI: 10.1080/13854040490501718
|View full text |Cite
|
Sign up to set email alerts
|

Practice Effect and Test-Retest Reliability of Attentional and Executive Tests in Middle-Aged to Elderly Subjects

Abstract: There is a lack of data about the practice effect and test-retest reliability (TRR) on many attentional and executive tests in neuropsychology. In this study, 37 subjects aged 52 to 80 were tested three times with an inter-assessment interval of 14 days. The battery included the Rey Auditory Verbal Learning Test, the Stroop interference test, the Letter-Number Sequencing test, Wechsler Adult Intelligence Scale-III (WAIS-III), the Ruff 2 and 7 Selective Attention Test, the Tower of London, the Verbal Fluency te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
114
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 72 publications
17
114
1
3
Order By: Relevance
“…There was a significant effect of treatment, independent of type (before treatment: 5.1 ± 5.1 words, after treatment: 6.5 ± 5.6 words, paired t = 2.55, p = 0.02), apparently related to practice (Figure 1). This is similar in magnitude to the practice effect observed in normal control subjects given repeated administrations of a verbal fluency task (Lemay et al, 2004). There was no significant effect of treatment on the Neuropsychiatric Inventory scores.…”
supporting
confidence: 77%
“…There was a significant effect of treatment, independent of type (before treatment: 5.1 ± 5.1 words, after treatment: 6.5 ± 5.6 words, paired t = 2.55, p = 0.02), apparently related to practice (Figure 1). This is similar in magnitude to the practice effect observed in normal control subjects given repeated administrations of a verbal fluency task (Lemay et al, 2004). There was no significant effect of treatment on the Neuropsychiatric Inventory scores.…”
supporting
confidence: 77%
“…Previous studies have indicated that in the elderly, improvement may occur at short time intervals especially between the first and the second assessment [38]. In this study, the tests were repeated at yearly intervals in four different evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 At least several of the tests used in our battery (i.e., Trail's test, Finger Tapping test, Digit Span forward, Reaction time) have been reported to lack significant practice effects. 35 To minimize potential practice effects in the current study, tests with alternate forms were selected whenever possible (e.g., 4 forms of the Selective reminding test) and the tests were administered in a predetermined order.…”
Section: Discussionmentioning
confidence: 99%